Arabic Learning Design Based on 21st Century Skills during the Covid-19 Pandemic in Indonesia - Susanto; Apri Wardana Ritonga; Ayu Desrani; Yohan Rubiyantoro (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The Covid-19 pandemic that hit Indonesia changed learning patterns from offline to online using technology as media. Hence, Arabic language learning must be well designed but still contains elements of 21st century life skills. This study aims to explore the design of 21st century skills-based Arabic learning which was held during the Covid-19 pandemic at Thursina International Islamic Boarding School Malang, Indonesia. This research adopts a qualitative approach with a case study method. Data were collected through observation, interviews, and document studies. The data collected were analyzed using the theory of Miles and Huberman, namely reducing, presenting, and verifying. Furthermore, the data is validated using data triangulation and data sources. This research shows that the implementation of 21st century skills can be done online during the Covid-19 pandemic; achievement indicators refer to the content of elements in 21st century skills known as 4C (critical thinking, communication, collaboration, and creativity & inovation) terminology; while the challenges of implementing 21st century skills stem from the skills of teachers in operating technology when presenting subject matter to students. The findings of this study describe that 21st century skills encourage students to become globally competitive human resources. The researcher recommends the next research to test the effectiveness of internalizing 21st century skills with online learning models. Keywords: Arabic Learning Design, Learning Design, Learning Arabic